Uranium. No. 03. Brinex and the Provincial Assessments Advisory Committee - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1977)
Dr. David Barnes of the Provincial Department of Consumer Affairs and the Environment talks about the Environmental Assessment Process and the Dames and Moores environmental impact study on the proposed Brinex uranium development. "Brinex and the Provincial Accessments Advisory Committee" Audio quality poor in places.